KETIKA MASA DEPAN MENANTI : STUDI TENTANG EFIKASI DIRI MAHASISWA TINGKAT AKHIR DI PULAU JAWA - Imelda Enerstine Waruwu; William Gunawan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The transition to the workforce requires final-year students to possess adequate self-confidence in making career decisions. This study aims to assess the level of Career Decision Making Self-Efficacy (CDMSE) among final-year students in Java as an indicator of work readiness. Employing a descriptive quantitative approach, the study involved 540 respondents selected via cluster quota sampling and utilized the valid and reliable Career Decision Making Self-Efficacy (CDMSE) instrument. The results indicate that the majority of students possess self-efficacy levels ranging from moderate to high. The occupational information dimension showed the highest scores, reflecting students' confidence in accessing and understanding information about the professional world. Conversely, the self-appraisal and planning dimensions yielded relatively lower scores, indicating a need for further strengthening. It is concluded that while final-year students in Java demonstrate reasonably good self-efficacy regarding career decision-making, higher education institutions need to bolster career guidance services particularly in developing self-reflection and career planning skills to better prepare graduates for the workforce. ABSTRAK Transisi menuju dunia kerja menuntut mahasiswa tingkat akhir memiliki keyakinan diri yang memadai dalam pengambilan keputusan karier. Penelitian ini bertujuan untuk memetakan tingkat Career Decision-Making Self-Efficacy (CDMSE) mahasiswa tingkat akhir di Pulau Jawa sebagai indikator kesiapan kerja. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan melibatkan 540 responden yang dipilih menggunakan teknik cluster quota sampling serta instrumen Career Decision Making Self-Efficacy (CDMSE) yang valid dan reliabel. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa memiliki tingkat efikasi diri pada kategori sedang hingga tinggi. Dimensi occupational information menunjukkan capaian tertinggi, yang mengindikasikan keyakinan mahasiswa dalam mengakses dan memahami informasi dunia kerja. Sebaliknya, dimensi self-appraisal dan planning memiliki capaian relatif lebih rendah sehingga masih memerlukan penguatan. Disimpulkan bahwa mahasiswa tingkat akhir di Pulau Jawa telah memiliki efikasi diri yang cukup baik dalam pengambilan keputusan karier, namun perguruan tinggi perlu memperkuat layanan bimbingan karier, terutama dalam pengembangan kemampuan refleksi diri dan perencanaan karier agar lulusan lebih siap menghadapi dunia kerja.